Implications of the Concept of Planning for Projects From the Perspective of Venezuelan Educational Actors - Pasek-de Pinto, Eva; Villamil-de Vásquez, Teresita; Ávila-de Vanegas, Nelly (Revista Electrónica Educare, 2017)
This article is the result of a research project which aimed to infer educational, epistemological, political and transforming implications from the conceptions educational stakeholders have about planning for projects. The study was addressed from the phenomenological philosophical school perspective with a qualitative methodology based on interviews. Following Rodríguez et al. (1999), the research was conducted in four stages: the preparatory phase, the field work, the analysis, and the information phase. In-depth interviews were carried out with three principals, eight teachers, four representatives and two students. The information gathered was transcribed, organized, codified, categorized by concepts, interpreted and triangulated. The results indicated that educational stakeholders understand planning by projects like a vision, an orderly sequence of steps, a collective action, an intention of achievement, a strategy, and a goal. From these ideas derived educational, epistemological, and political implications for change. It is concluded that the conceptions of educational stakeholders on planning for projects render difficult an education for a participatory democracy, for action, and for change, limiting the formation of the new cooperative and responsible citizenship. Therefore it is suggested to train teachers for participation since they ensure the educational process.